2020
DOI: 10.1038/s41467-020-19700-1
|View full text |Cite
|
Sign up to set email alerts
|

Dinucleosome specificity and allosteric switch of the ISW1a ATP-dependent chromatin remodeler in transcription regulation

Abstract: Over the last 3 decades ATP-dependent chromatin remodelers have been thought to recognize chromatin at the level of single nucleosomes rather than higher-order organization of more than one nucleosome. We show the yeast ISW1a remodeler has such higher-order structural specificity, as manifested by large allosteric changes that activate the nucleosome remodeling and spacing activities of ISW1a when bound to dinucleosomes. Although the ATPase domain of Isw1 docks at the SHL2 position when ISW1a is bound to eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 64 publications
2
11
0
Order By: Relevance
“…Of these, rNCPs provide a unique tool to study how nucleosome assembly and specific histone marks affect enzyme activity. Recently, chromatin-remodeling/modifying complexes were found to exhibit different specificity toward mononucleosomes and dinucleosomes, highlighting their higher-order structural specificity ( Poepsel et al, 2018 ; Bhardwaj et al, 2020 ). We thus used rNCPs to assess whether the activity of the native NuA4/TIP60 complex is affected by the structural differences between the two types of rNCPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, rNCPs provide a unique tool to study how nucleosome assembly and specific histone marks affect enzyme activity. Recently, chromatin-remodeling/modifying complexes were found to exhibit different specificity toward mononucleosomes and dinucleosomes, highlighting their higher-order structural specificity ( Poepsel et al, 2018 ; Bhardwaj et al, 2020 ). We thus used rNCPs to assess whether the activity of the native NuA4/TIP60 complex is affected by the structural differences between the two types of rNCPs.…”
Section: Resultsmentioning
confidence: 99%
“…First, we describe the use of the 3 × FLAG-2 × Strep tag fused to a gene of interest (either expressed from AAVS1 or endogenously tagged) to purify native chromatin modifying complexes for biochemical/enzymatic assays. Second, we provide a step-by-step protocol for the production of recombinant mono- and di-nucleosomes, the latter having particular potential since recent studies have highlighted the importance of linker DNA in the mechanisms of many remodelers and modifiers ( Poepsel et al, 2018 ; Bhardwaj et al, 2020 ). Finally, we present a new rapid depletion approach for mammalian cells, inspired by the yeast anchor-away system ( Haruki et al, 2008 ).…”
Section: Approaches To Characterize Chromatin-modifying Enzyme Activities and Functionsmentioning
confidence: 99%
“…Reactions were stopped with 172 μL of 2xSTOP solution (10mM Tris, 2mM MgCl 2 , 340mM NaCl, 20mM EDTA, 4mM EGTA, 100ug/mL RNase, DNase-free (Sigma11119915001) and DNA was extracted as described below. For reconstituted nucleosomes, we digested with 0.2 U MNase/μg DNA for 7 min at room temperature (Bhardwaj et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…These unique dynamics of dinucleosomes may relate to the ability of remodelers to recognize them. For example, it has been reported that Isw1a prefers to bind dinucleosomes rather than mononucleosomes and its binding affinity to the dinucleosome can be elevated by increasing the distal DNA arm length of the array regardless of histone modifications 49 . Also, SWI/SNF shifts the dinucleosome positions faster than those of trinucleosomes, as shown by electrophoresis assays 50 .…”
Section: Effect Of Ncp Number On Nucleosome Array 3d Structural Dynamicsmentioning
confidence: 99%